Functional Characterization and Signaling Systems of Corazonin and Red Pigment Concentrating Hormone in the Green Shore Crab, Carcinus maenas - Alexander, Jodi L.; Oliphant, Andrew; Wilcockson, David C.; Audsley, Neil; Down, Rachel E.; Lafont, Rene; Webster, Simon G. (Frontiers in Neuroscience, 2018)
Neuropeptides play a central role as neurotransmitters, neuromodulators and hormones in orchestrating arthropod physiology. The post-genomic surge in identified neuropeptides and their putative receptors, has not been matched by functional characterization of ligand-receptor pairs. Indeed, until very recently no G protein-coupled receptors (GPCRs) had been functionally defined in any crustacean. Here we explore the structurally related, functionally diverse gonadotropin-releasing hormone paralogs, corazonin (CRZ) and red-pigment concentrating hormone (RPCH) and their G-protein coupled receptors (GPCRs) in the crab, Carcinus maenas. Using aequorin luminescence to measure in vitro Ca2+ mobilization we demonstrated receptor-ligand pairings of CRZ and RPCH. CRZR activated cell signaling in a dose-dependent manner (EC50 0.75nM) and comparative studies with insect CRZ peptides suggest that the C-terminus of this peptide is important in receptor-ligand interaction. RPCH interacted with RPCHR with extremely high affinity (EC50 20pM). Neither receptor bound GnRH, nor the AKH/CRZ-related peptide. Transcript distributions of both receptors indicate that CRZR expression was, unexpectedly, restricted to the Y-organs (YO). Application of CRZ peptide to YO had no effect on ecdysteroid biosynthesis, excepting a modest stimulation in early post-molt. CRZ had no effect on heart activity, blood glucose levels, lipid mobilization or pigment distribution in chromatophores, a scenario that reflected the distribution of its mRNA. Apart from the well-known activity of RPCH as a chromatophorotropin, it also indirectly elicited hyperglycemia. RPCHR mRNA was also expressed in the ovary, indicating possible roles in reproduction. The architecture of CRZ and RPCH neurons in the nervous system is described in detail by immunohistochemistry and in situ hybridization. Each peptide has extensive but non-overlapping distribution in the CNS, and both are released from the post-commissural organs. This study is one of the first to deorphanize a GPCR in a crustacean and to provide evidence for hitherto unknown and diverse functions of these evolutionarily related neuropeptides.